SCHOOL PRINCIPAL ACCOUNTABILITY IN IMPROVING TEACHER COMPETENCY STATE TSANAWIYAH MADRASAH IN JAMBI PROVINCE - Muttaqin; Muntholib, SM; Abd. Malik (European Journal of Humanities and Educational Advancements, 2023)
This research aims to determine the accountability of school principals in improving the competency of state Islamic secondary school teachers in Jambi Province by discussing the accountability of school principals and teacher personality competencies first. This research uses a qualitative approach by carrying out observations, interviews, and documentation to collect data and analyze it by collecting data, reducing data, presenting data, and ending by verifying the data. Meanwhile, triangulation is used as a technique to ensure the validity of the data. The research results obtained from three schools show that there is quite a big commitment of each school principal, then there is quite good transparency of the principal, then the achievements of the principal are quite high and an indication of community satisfaction with the principal’s performance is also quite high. . Based on the research results, it can be concluded that there is accountability of school principals in improving the personality competence of State Madrasah Tsanawiyah teachers in Jambi Province with commitment, transparency, achievement and community satisfaction which are considered quite large.